Ex vivo perfusion induces a time‐ and perfusate‐dependent molecular repair response in explanted porcine lungs. Issue 4 (8th October 2018) - Dromparis, Peter; Aboelnazar, Nader S.; Wagner, Siegfried; Himmat, Sayed; White, Christopher W.; Hatami, Sanaz; Luc, Jessica G. Y.; Rotich, Silas; Freed, Darren H.; Nagendran, Jayan; Mengel, Michael; Adam, Benjamin A.
Abstract : Ex vivo lung perfusion (EVLP) shows promise in ameliorating pretransplant acute lung injury (ALI) and expanding the donor organ pool, but the mechanisms of ex vivo repair remain poorly understood. We aimed to assess the utility of gene expression for characterizing ALI during EVLP. One hundred sixty‐nine porcine lung samples were collected in vivo (n = 25), after 0 (n = 11) and 12 (n = 11) hours of cold static preservation (CSP), and after 0 (n = 57), 6 (n = 8), and 12 (n = 57) hours of EVLP, utilizing various ventilation and perfusate strategies. The expression of 53 previously described ALI‐related genes was measured and correlated with function and histology. Twenty‐eight genes were significantly upregulated and 6 genes downregulated after 12 hours of EVLP. Aggregate gene sets demonstrated differential expression with EVLP ( P < .001) but not CSP. Upregulated 28‐gene set expression peaked after 6 hours of EVLP, whereas downregulated 6‐gene set expression continued to decline after 12 hours. Cellular perfusates demonstrated a greater reduction in downregulated 6‐gene set expression vs acellular perfusate ( P < .038). Gene set expression correlated with relevant functional and histologic parameters, including P/F ratio ( P < .001) and interstitial inflammation ( P < .005). Further studies with posttransplant results are warranted to evaluate the clinical significance of this novel molecular approach for assessing organ quality during EVLP. Abstract : Gene expression analysis of explanted porcine lungs demonstrates that ex vivo perfusion induces a time‐ and perfusate‐dependent molecular repair response, which correlates with relevant functional and histological parameters.